Implementasi Pengaturan Jarak Tendangan Prototipe Kaki Robot pada Kaki Manusia Menggunakan Sensor Gyroscope dan Accelerometer dengan Metode PID - Jodie Putra Kahir; Wijaya Kurniawan; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In today's age there are many people from various circles and age levels who love to play games. Games that are usually played are divided on several platforms one of which is a console platform. But on the console platform it seems there is still a lack of type of interaction that can be done by users with games on the console. Then came the idea that to add the kind of interaction between the user and the game football on the console, which is a system that can regulate the power of the user's kick while playing. In the manufacture of kick power settings on the robot leg prototype is required several components. Such components include Gyroscope & Accelerometer (MPU-6050 sensor), Arduino Nano, IBT Motor Driver, DC Motor, and a prototype of robot legs. And also the power settings of this robot kick also use PID method as a controller. In testing the distance kicks, successfully drawn the conclusion that the smaller the degree value of inclination on the sensor the further distance kick that can be done by robot legs prototype. And on testing the overall control system managed to get the value of L = 1.67s and T = 13.91 which then used the formula Zieger Nicolas 1 to get the value Kp = 8.33; Ki = 2.49; and Kd = 0.69.